2023
DOI: 10.5194/tc-17-1697-2023
|View full text |Cite
|
Sign up to set email alerts
|

Bedfast and floating-ice dynamics of thermokarst lakes using a temporal deep-learning mapping approach: case study of the Old Crow Flats, Yukon, Canada

Abstract: Abstract. In light of the recent climate warming, monitoring of lake ice in Arctic and subarctic regions is becoming increasingly important. Many shallow Arctic lakes and ponds of thermokarst origin freeze to the bed in the winter months, maintaining the underlying permafrost in its frozen state. However, as air temperatures rise and precipitation increases, fewer lakes are expected to develop bedfast ice. In this work, we propose a novel temporal deep-learning approach to lake ice regime mapping from syntheti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 58 publications
0
0
0
Order By: Relevance
“…In addition, the waterbody mask may not align perfectly with the current lakeshores and contribute to land being classified as FI or BFI. As for the isolated patches of BFI classed in the middle of deeper lakes, these have been observed in other studies(Duguay and Wang 2019;Shaposhnikova et al 2023). Overestimation of BFI in these areas remains a challenge and is possibly due to ice cracking or local thinning(Pointner et al 2019; Pointner and Barsch 2020).…”
supporting
confidence: 65%
See 1 more Smart Citation
“…In addition, the waterbody mask may not align perfectly with the current lakeshores and contribute to land being classified as FI or BFI. As for the isolated patches of BFI classed in the middle of deeper lakes, these have been observed in other studies(Duguay and Wang 2019;Shaposhnikova et al 2023). Overestimation of BFI in these areas remains a challenge and is possibly due to ice cracking or local thinning(Pointner et al 2019; Pointner and Barsch 2020).…”
supporting
confidence: 65%
“…Airborne and satellite SAR imagery have been applied to shallow lakes to get knowledge on lake ice regime and thickness, lake depth, and indirectly to assess permafrost and thermokarst processes, methane gas emissions, overwintering fish habitat, and freshwater availability for regions in Alaska, northern Manitoba, Mackenzie Delta, and Russia, and at the circumpolar scale (Murfitt and Duguay 2021). Threshold-based methods using C-band co-polarized signals (HH and VV) are the most common approaches used to classify FI and BFI (van der Sanden et al 2012;Engram et al 2018;Murfitt and Duguay 2021;Shaposhnikova et al 2023). These methods use the difference in backscatter between FI and BFI to identify threshold(s) capable of differentiating between the two types of ice cover.…”
Section: Introductionmentioning
confidence: 99%
“…For sea ice, the total σ o typically consists of surface scattering from the snow surface, volume scattering from the snow layer, surface scattering from the ice surface and scattering from the air bubbles and brine pockets in the ice medium. For lake ice, there is more volume scattering from the lower layers of the ice; surface scattering from internal layers in the ice, scattering from the ice-water surface and double-bounce scattering from the bottom bubbled ice layer are included as well [56,57]. In recent studies, the scattering caused by the roughness of the ice-water interface has been found to be the primary contribution to the total scattering over lake ice and not the double bounce from air bubbles, as has been assumed previously [46,58].…”
Section: Previous Studiesmentioning
confidence: 99%
“…For sea ice, the total σ o typically consists of surface scattering from the snow surface, volume scattering from the snow layer, surface scattering from the ice surface and scattering from the air bubbles and brine pockets in the ice medium. For lake ice, there is more volume scattering from the lower layers of the ice, surface scattering from internal layers in the ice, scattering from the ice-water surface and double-bounce scattering from the bottom bubbled ice layer are included as well [42,43]. In recent studies, the scattering caused by the roughness of ice/water interface has been found to be the primary contribution to the total scattering over lake ice and not the double bounce from air bubbles, as has been assumed previously [29,44].…”
Section: Figurementioning
confidence: 99%